Ultrasonic attenuation anomalies of n-type superconductor Pr2−xCexCuO4 - Chong, Tet Vui*; Abd Shukor, R. (World Scientific Publishing Co Pte Ltd, 2016)
Pr2−x2−xCexxCuO4 (xx = 0 and 0.15) samples were prepared via solid state reaction. Pr2CuO4 sample is insulating while Pr1.851.85Ce0.150.15CuO4 sample exhibited an onset critical temperature, TcTc of 21 K. The temperature dependences of ultrasonic attenuation in these polycrystalline n-type superconductor Pr2−x2−xCexxCuO4 (xx = 0 and 0.15) samples have been measured between 80 K and 300 K using longitudinal and shear waves by pulse-echo-overlap method with frequencies between 5 MHz and 10 MHz. For the longitudinal mode, a pronounced attenuation peak around 200 K was observed in Pr2CuO4, but it is not observed in the superconducting material Pr1.851.85Ce0.150.15CuO4. For the shear mode, no pronounced attenuation peaks were observed in the samples. It is suggested that the attenuation peak in the xx = 0 sample at 200 K is due to the weak structural distortion induced by the magnetic transition.